Automated Dispatch of Wind Power On Microgrid For Voltage Regulation (International Journal of Automation and Smart Technology, 2025)
It is proposed that Home Automation systems would be vastly improved by the novel approach of eliminating the permanent central controller as it is the source of significant problems. This leaves the responsibilities of the permanent central controller to be assumed by the remaining devices in the system, including IoT devices and interface devices such as smartphones and computers. While the capacity for joining devices to a network without the permanent central controller has been considered, device discovery has not. This paper examines existing protocols but finds that while many have worthwhile aspects none are suitable for the task. A novel discovery protocol is proposed, using smartphones or computers as intermittent control devices. This new protocol is developed with the aid of a new Robust Network Development Methodology which is able to anticipate problematic use cases prior to implementation. This methodology was very successfully in identifying and eliminating significant problems with the new protocol. Implementation and measurement of the novel discovery protocol demonstrates the viability and robustness of discovery without a permanent central controller on low cost ESP8266 family devices.